CFD simulation of modified solar still for effective condensation and evaporation: energy and exergy analysis - Kumar, Rajesh; Kumar, Laveet; Mirjat, Nayyar Hussain; Harijan, Khanji (Frontiers in Water, 2024)
Water scarcity is a global challenge, underscoring the importance of efficient water resource management. Solar stills offer a cost-effective method to convert brackish water into potable water but face productivity limitations. This study aims to enhance solar still productivity through modifications using different fin materials and water depth. Computational Fluid Dynamics (CFD) simulations were employed to evaluate thermal performance across four scenarios: copper and aluminum fins at water depths of 20 mm and 40 mm. Key parameters including temperature distributions, friction volume, and fluid velocity were analyzed for each configuration (MSS-I to MSS-IV). Energy and exergy efficiencies were also assessed. MSS-III, utilizing copper fins at a 20 mm depth, demonstrated the highest daily productivity (8.33 liters) compared to MSS-IV (8.02 liters), MSS-I (7.81 liters), and MSS-II (6.71 liters). Energy efficiencies were highest for MSS-III (60.10%), followed by MSS-IV (57.41%), MSS-I (55.22%), and MSS-II (52.18%). MSS-III also exhibited the highest exergy efficiency (21.50%), with MSS-I (17.15%), MSS-IV (16.43%), and MSS-II (14.12%) following. The study underscores significant improvements in thermal and energy efficiency achieved through specific design modifications of solar stills. MSS-III’s higher performance, attributed to the use of copper fins and optimized depth, highlights the critical role of material selection and structural design in enhancing solar still productivity. These findings have important implications for sustainable water resource management, emphasizing the potential of optimized solar still designs to address water scarcity challenges.